(untitled) (Historia, 2021)
The movement of human experience from one point in time to another is elemental to the study of history. Progress in history has been analysed in linear, cyclical and sequential frames of reference, which have been refuted by historians for various reasons. Another method not yet employed by historians is to look at conceptualising the effect of the combination of the theories of relativity and quantum physics by Stephen Hawking in his work entitled : A brief History of time. This is not to suggest that history follows pathways which humans can accurately determine as some of the laws in physics do. History should propose and motivate itself as a science with its own identity and forms of enquiry but cannot total remove itself from general scientific discourse?